Penerapan Regulasi IMO (International Maritime Organization) Terkait Pengolahan Air Ballast dan Pengaruhnya Terhadap Permesinan Kapal - Pereira Maia Pinto, Gaspar (Blueprint Journal, 2025)
This study analyzes the impact of the implementation of the International Maritime Organization (IMO) regulations regarding ballast water treatment on ship machinery technology and operations. Results show that technologies such as filtration, UV disinfection and electrochlorination effectively meet environmental standards, but increase energy consumption by up to 10% and require complex integration with ship systems. These regulations also affect operational procedures, maintenance frequency, and crew training, adding to the operational burden. This study offers recommendations to improve efficiency and compliance with IMO standards.